135k views
5 votes
Use elimination to solve the following system of
equations: 17x - 2y = 25
17x + 3y = 5

1 Answer

5 votes

Explanation:


17x - 2y = 25


17x + 3y = 5

Both equations have a
17x term in them, so if we subtract the second equation from the first, it will eliminate those terms, allowing us to solve for the remaining
y terms:


(17x - 2y) - (17x + 3y) = 25 - 5


(17x - 17x) + (-2y - 3y) = 20


-5y = 20


y = -4

Finally, we can plug this value for
y into either of the two original equations to solve for
x:


17x - 2(-4) = 25


17x + 8 = 25


17x = 17


x = 1

This means the solution to the system of equations is
(1, -4).

User Analee
by
6.3k points